2012
DOI: 10.1021/ja301539s
|View full text |Cite
|
Sign up to set email alerts
|

CsSnI3: Semiconductor or Metal? High Electrical Conductivity and Strong Near-Infrared Photoluminescence from a Single Material. High Hole Mobility and Phase-Transitions

Abstract: CsSnI(3) is an unusual perovskite that undergoes complex displacive and reconstructive phase transitions and exhibits near-infrared emission at room temperature. Experimental and theoretical studies of CsSnI(3) have been limited by the lack of detailed crystal structure characterization and chemical instability. Here we describe the synthesis of pure polymorphic crystals, the preparation of large crack-/bubble-free ingots, the refined single-crystal structures, and temperature-dependent charge transport and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

92
1,126
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 992 publications
(1,225 citation statements)
references
References 42 publications
92
1,126
4
3
Order By: Relevance
“…Fit over a temperature range of 200 K to 299 K, αV is greater than 200 × 10 -6 K -1 (R 2 = 99.8%). Thus, αV for the β-phase is larger than that for liquid mercury [21] and appears to be nearly the largest for any extended crystalline solid near ambient temperature. It was recently reported that αV = 220 × 10 -6 K -1 for the mixed A-site [CH3NH3]0.5[HC(NH2)2]0.5PbI3, though the precise temperature and fitting range are unspecified.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Fit over a temperature range of 200 K to 299 K, αV is greater than 200 × 10 -6 K -1 (R 2 = 99.8%). Thus, αV for the β-phase is larger than that for liquid mercury [21] and appears to be nearly the largest for any extended crystalline solid near ambient temperature. It was recently reported that αV = 220 × 10 -6 K -1 for the mixed A-site [CH3NH3]0.5[HC(NH2)2]0.5PbI3, though the precise temperature and fitting range are unspecified.…”
mentioning
confidence: 89%
“…The increased values of the U┴ ADPs on cooling to the γ-phase suggest disorder that is not fully captured by this crystallographic model. [19,20] CsSnI3 γ (solid) 298 126 [21] Ag3[Co(CN)6] Solid 276 121 [22] Hg Liquid 293 182 [21] The unit cell volume per formula unit, V, is given in Figure 4(a). A comparison of the volumetric thermal expansion coefficient, αV, with those of other main-group halides and selected framework materials and liquids is given in Table 1.…”
mentioning
confidence: 99%
“…Replacing the organic cations (MA + or FA + ) with the inorganic Cs + , CsSnI 3 perovskite shows a melting point of 435 °C,72, 141 suggesting superior intrinsic thermal stability. In contrast, hybrid perovskites MASnI 3 and FASnI 3 start to decompose at ≈200 °C.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
“…Due to the 4s lone pairs of Ge is more active than the Pb 6s lone pair, Ge 2+ is easier to be oxidized leading to metallic conductivity in the hybrid materials and short‐circuit behavior in the photovoltaic devices similar to the case of Sn‐based perovskite 40, 135, 141. However, germanium has demonstrated much less toxicity compared to lead146 and is expected to be a promising candidate in the search for Pb‐free perovskite materials.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 1 more Smart Citation